ACCUMULATED DEPRECIATION–BALANCE SHEET PRESENTATION. - Leonard, W. G. (The Accounting Review, 1959)
Abstract The article by professor Sidney I. Simon entitled "The Right Side of Accumulated Depreciation" stimulated the interest of accounting theorist. The author, a Canadian accountant, subscribes to the doctrine enunciated by Bulletin No. 9 of the Committee on Accounting and Auditing Research of the Canadian Institute of Chartered Accountants in 1953 which states that the term "reserve" is inappropriate as a description of accumulated depreciation and that this use of the term "reserve" has led to misunderstanding of financial statements. Simon, in the article cited, states that the arguments of some protagonists of the asset-deduction approach, which he opposes, are "quite negative in nature." Then he adopts a double negative approach by devoting a large part of his article to combating negative-type arguments. This author will attempt to eschew all negative reasoning and to advance positive reasons to support the viewpoint he adopts. Simon argues that many readers of balance sheets are given "the false impression that the net asset figure represents its value.